2022
DOI: 10.3390/cancers15010266
|View full text |Cite
|
Sign up to set email alerts
|

Theranostic Applications of Glycosaminoglycans in Metastatic Renal Cell Carcinoma

Abstract: Renal cell carcinoma (RCC) makes up the majority of kidney cancers, with a poor prognosis for metastatic RCC (mRCC). Challenges faced in the management of mRCC, include a lack of reliable prognostic markers and biomarkers for precise monitoring of disease treatment, together with the potential risk of toxicity associated with more recent therapeutic options. Glycosaminoglycans (GAGs) are a class of carbohydrates that can be categorized into four main subclasses, viz., chondroitin sulfate, hyaluronic acid, hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 191 publications
0
8
0
Order By: Relevance
“…Various investigations of PG/GAG in the oral cavity reported either expression or potential involvement of these factors in the progression of oral squamous cell carcinoma and salivary tumors. 21 As for odontogenic tumors, CS PG is widely observed but variably expressed in epithelial nests and stroma of both AM and keratocystic odontogenic tumor, and the keratocystic odontogenic tumors have been renamed odontogenic keratocyst in the 2017 World Health Organization (WHO) classification of head and neck tumors. 22 In our present study, the alterations of PG, heparin sulfate, and glycosaminoglycan were enriched in both GO and KEGG pathway analyses and may be associated with the molecular pathogenesis of AM.…”
Section: Discussionmentioning
confidence: 99%
“…Various investigations of PG/GAG in the oral cavity reported either expression or potential involvement of these factors in the progression of oral squamous cell carcinoma and salivary tumors. 21 As for odontogenic tumors, CS PG is widely observed but variably expressed in epithelial nests and stroma of both AM and keratocystic odontogenic tumor, and the keratocystic odontogenic tumors have been renamed odontogenic keratocyst in the 2017 World Health Organization (WHO) classification of head and neck tumors. 22 In our present study, the alterations of PG, heparin sulfate, and glycosaminoglycan were enriched in both GO and KEGG pathway analyses and may be associated with the molecular pathogenesis of AM.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the adverse effects caused by heparin, such as bleeding and thrombocytopenia [ 168 ], intense research studies have been performed to develop heparin analogs or HS mimetics with no anticoagulant activities and fewer side effects. In this regard, and based on the impressive data of their anticancer effects in preclinical models, the HS mimetics muparfostat (PI-88), pixatimod (PG545), and necuparanib (M402) entered clinical trial phases I, II, and III alone or in combined therapy to evaluate their safety and beneficial effects on the survival of a patient with different advanced solid cancers and multiple myeloma (reviewed in [ 165 , 169 ]). The mechanism of action of these HS-mimetics is primarily mediated via inhibition of heparanase-mediated angiogenesis and metastasis, competitive binding with growth factors, and/or activation of tumor-suppressing immune cells (e.g., natural killer and dendritic cells) [ 165 , 169 ].…”
Section: Syndecans As Targets For Breast Cancer Therapiesmentioning
confidence: 99%
“…In this regard, and based on the impressive data of their anticancer effects in preclinical models, the HS mimetics muparfostat (PI-88), pixatimod (PG545), and necuparanib (M402) entered clinical trial phases I, II, and III alone or in combined therapy to evaluate their safety and beneficial effects on the survival of a patient with different advanced solid cancers and multiple myeloma (reviewed in [ 165 , 169 ]). The mechanism of action of these HS-mimetics is primarily mediated via inhibition of heparanase-mediated angiogenesis and metastasis, competitive binding with growth factors, and/or activation of tumor-suppressing immune cells (e.g., natural killer and dendritic cells) [ 165 , 169 ]. An interesting study showed that in an ex vivo explant model of normal human female mammary tissue, heparanase upregulates the expression and cleavage of SDC1 rather than SDC4, resulting in high mammographic density (a strong and independent risk factor for breast cancer) with a fibrous stroma rich in SDC1.…”
Section: Syndecans As Targets For Breast Cancer Therapiesmentioning
confidence: 99%
“…Moreover, while each drug alone is ineffective at its pharmacological dose, the combination effectively eliminates metastasis, thus making an old, failed drug like Sorafenib effective again. Previous works by this group and others showed that HAS3 and related molecules are highly elevated in genitourinary tumors and promote tumor growth, angiogenesis, metastasis, and treatment-induced resistance [ 6 - 22 ]. Therefore, the mechanisms and the targets identified in the studies by Jordan et al and Wang et al should likely have a broad clinical implication.…”
Section: Introductionmentioning
confidence: 99%